Discourse Tact in Doctor-Patient Interactions in English: An Analysis of Diagnosis in Medical Communication in Nigeria - Adegbite, Wale; Odebunmi, Akin (2014)
This study describes discourse tact in diagnoses in doctor-patient interactions in English in selected hospitals in South-western Nigeria. Using recorded conversations between doctors and patients in those hospitals as data, the mutual contextual beliefs of participants, speech act patterns, including linguistic patterns, and other pragmatic features are analyzed from the perspective of the pragmatics of discourse. The findings indicate the predominance of doctor-initiated spoken exchanges in which doctors elicit and confirm information and give directives to patients, while the patients give information and attempt to respond appropriately to the doctors' moves. It is also observed that conversation maxims are flouted and politeness maxims exploited in order to enhance successful diagnosis in the interaction. Finally, it is observed that doctor-patient interaction is only one out of many aspects of medical communication that require the attention of language scholars in order to gain insight into language as an act of social behaviour and action, especially with respect to the institution of medicine.